Information society and the workplace : spaces, boundaries and agency - Heiskanen, Tuula; Hearn, Jeff, 1947- (London ; New York : Routledge, 2004)
Bringing together studies of everyday local practices in workplaces within information society, this book has a special focus on social space and the agency of actors. it includes both theoretical reviews and qualitative research.
Book Cover; Title; Contents; Notes on contributors; Preface: paradoxes of information, society and workplaces; Acknowledgements; Spaces, places and communities of practice; Bounded or empowered by technology? Information system specialists' views on people's freedom within technology; Gendered local agency: the development of regional information society; Empty spaces without knowledge and management; The dynamics of control and commitment in IT firms; Virtualizing the office: micro-level impacts and driving forces of increased ICT use; Women and technological pleasure at work?
Includes bibliographical references (pages 209-225) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Information society; Industrial sociology; Société de l'information.; Sociologie industrielle; COMPUTERS -- Information Technology; Industrial sociology; Information society; Informationssamhället.; Kunskapsöverföring.